Tourism destination image of Aqaba in the digital age: A user-generated content analysis of cognitive, affective, and conative elements - Alzboun, Nidal; Khawaldah, Hamzah; Harb, Ayman; aburumman, Asad (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to evaluate the image of Aqaba as a key tourist destination in Jordan through the analysis of tourist reviews on TripAdvisor, the largest user-generated content (UGC) platform for travel. TripAdvisor allows insights into a destination’s image from the perspective of actual visitors. Utilizing NVivo 12 software, both content and sentiment analyses were conducted on reviews found in the TripAdvisor Forum for Aqaba. The findings highlight the significance of the cognitive, affective, and conative components of Aqaba’s destination image. These elements were examined to determine whether reviewers identified aspects of the destination related to cognitive knowledge (e.g., attractions and infrastructure), emotional responses (e.g., enjoyment or dissatisfaction), or behavioral intentions (e.g., revisits or recommendations). Additionally, each image component was rated positively or negatively based on the review content. The study’s results provide valuable insights for decision-makers and planners, including those at the Ministry of Tourism and Antiquities and the Aqaba Special Economic Zone Authority, to better tailor their strategies to improve the destination’s appeal.